Towards Dendrite‐Free Potassium‐Metal Batteries: Rational Design of a Multifunctional 3D Polyvinyl Alcohol‐Borax Layer. (12th October 2021) - Wang, Shuo; Yan, Yaping; Xiong, Dongbin; Li, Guojing; Wang, Ye; Chen, Fuming; Chen, Song; Tian, Bingbing; Shi, Yumeng
Abstract: K metal is the optimal anode for K‐ion batteries because of its high capacity and low operating potential, but it suffers from fast capacity fading and safety issues due to an unstable solid electrolyte interphase (SEI) and continuous K‐dendrite growth. Herein, to obtain promising potassium‐metal batteries, a 3D polyvinyl‐alcohol (PVA)‐borax layer is designed, which enables a dendrite‐free K‐plating/stripping process. The protective layer possesses good wettability, high K‐ion diffusivity, and good structural stability, which enables a "uniform and underneath plating" behavior, therefore exhibiting a stable electrochemical performance. As a result, Cu current collector with PVA‐borax (PVA‐borax@Cu) exhibits a stable cycling lifetime for 700 h at 0.5 mA cm −2 and 500 h at 1 mA cm −2 at 10 % depth of discharge (DOD) without dendrite formation. Even at a high utilization of 25 % DOD and 50 % DOD, the PVA‐borax@Cu shows a stable cycle for 180 h and 100 h, respectively. Abstract : A functional 3D cross‐linked polyvinyl‐alcohol‐borax layer possesses good electrolyte wettability, K‐ion diffusivity, and structural stability, enabling a stable K plating and stripping process for more than 700 h of cycling without dendrite formation.